Cost-effectiveness analysis for implementation of smoking cessation strategies at primary health care settings in Tamil Nadu - Vasantha Mahalingam; Ramesh Kumar Santhanakrishnan; Muniyandi Malaisamy; Karthick Chelvanayagam; Kavi Mathiyazhagan; Adhin Bhaskar; Karikalan Nagarajan; Jerard Maria Selvam; Surendran Veeraiah; Kavitha Rajsekar; Kirti Tyagi; Ponnuraja Chinnaiyan (PLoS ONE, 2025)
Background Smoking is a major public health concern in Tamil Nadu, as it is in many parts of the world. It is a leading cause of preventable diseases and deaths, with a significant economic burden on healthcare systems and society as a whole. Recognizing the need to address this issue, the implementation of smoking cessation strategies at primary health care (PHC) settings has gained attention. Conducting a cost-effectiveness analysis in this context can help policymakers and healthcare providers make informed decisions about the allocation of resources for such interventions. Objectives To compare the cost-effectiveness of the smoking cessation of proposed strategies (PSs), PS1: enhanced counselling (EC) + nicotine replacement therapy (NRT) + bupropion tablet; PS2: behavioural intervention (BI) + NRT + promotion of bupropion sustained release (SR); PS3: EC + NRT + promotion of bupropion SR with the current strategy (BI +NRT+ Bupropion) in a population of smokers aged ≥15 years attending the PHC in Tamil Nadu. Methods In this hypothetical cohort of 100,000 individuals using the decision tree analysis, a cost-effectiveness assessment was conducted for both proposed and existing strategies. The results were evaluated in terms of incremental cost-effectiveness ratios (ICERs) per person quitting smoking. To assess the robustness of the findings, one-way sensitivity analysis and probabilistic sensitivity analysis were performed which aims to explore and address the uncertainties associated with the outcomes. Results The cost of the current strategy (CS) was higher (₹359 or $4.28 million) when compared with PS1 (₹327 or $3.90 million) and PS3 (₹327 or $3.90 million) strategies. The PS2 with BI + bupropion SR + NRT was found to be more cost (₹2,720,571 or $ 32,414.76) as compared to current strategy. ICER values indicates that compared to the current strategy, the PS1 and PS3 were found to be cost-saving, whereas the PS2 was found to be cost-effective. The cost-effectiveness acceptability curve demonstrated that the PS1 and PS3 indicates 100% probability of the intervention being cost-saving. After excluding dominated interventions (PS2 and CS), the remaining strategies (PS1 and PS3) were compared. The PS3, with an incremental cost of ₹462,497 ($5,510) for 131 additional quitters, resulted in an ICER of ₹3,531 ($42) per quitter, making it a cost-effective option compared to PS1. Conclusion Our study findings indicate that the need for healthcare providers and policymakers to implement PS3 with EC, NRT, Bupropion SR, as which was found to be cost-saving compared to current practices.